Sustainable investment funds in India: a synthesis of the academic literature - Hooda, Sanjay Kumar; Sharma, Vipin (Journal of Social Review and Development, 2025)
Sustainable Investment Funds offer investors alternatives to invest their savings in shares of companies from a different perspective, extending the conventional medium of investing. These mutual funds encourage investors to consider the environment and society in which they live while investing in the stock market. This paper aims to review the existing literature on sustainable investment funds. Sixteen research papers selected from different countries are thoroughly studied. The findings reveal that the concept of SIFs is continuously increasing and gaining popularity. SIFs outperformed conventional funds, particularly in the wake of the COVID-19 outbreak. Some studies have supported the notion that non-SIFs outperform SIFs. However, when investors consider societal and environmental factors while making an investment, they are willing to sacrifice commercial or economic benefits in favor of social benefits.